Does respiratory variation in inferior vena cava diameter predict fluid responsiveness in adult patients? A systematic review and meta-analysis of diagnostic accuracy studies - AKOĞLU, HALDUN (My University, 2021)
Objectives: To systematically review the diagnostic utility of the respiratory variation of the inferior vena cava diameter measured using ultrasonography for predicting fluid responsiveness in adult patients and compare the three commonly used equations, inferior vena cava distensibility, inferior vena cava collapsibility and inferior vena cava variability. Methods: We searched PubMed, Scopus, Web of Science and Cochrane library, and included studies investigating the diagnostic accuracy of the respiratory variation of the inferior vena cava measured using ultrasonography compared to a reference standard for measuring cardiac output after a fluid challenge for fluid responsiveness, and stratified participants as fluid responsive or not. We included studies conducted in the emergency department or intensive care unit. We excluded studies on paediatric, prehospital, cancer, pregnant, dialysis patients or healthy volunteers. Results: We retrieved 270 records and excluded 171 because of irrelevance, patient population or publication type. We screened the abstracts of 99 studies and then the full texts of 42 studies. Overall, 21 studies with 1321 patients were included, of whom 689 (52%) were fluid responsive. The mean threshold value for positive inferior vena cava distensibility, inferior vena cava collapsibility and inferior vena cava variability was 17%, 35% and 12%, respectively. The heterogeneity between studies was high. Bivariate diagnostic random-effects meta-analysis was used to calculate the summary receiver operating characteristics curves. The overall accuracy, sensitivity and specificity of respiratory variation of the inferior vena cava diameter were 0.85, 0.72 and 0.81, respectively. The accuracy of inferior vena cava distensibility and inferior vena cava collapsibility was similar. The diagnostic utility of respiratory variation of the inferior vena cava diameter was lower but not statistically significant in mechanically ventilated patients compared with spontaneous breathing for predicting fluid responsiveness. Conclusion: The respiratory variation of the inferior vena cava diameter has moderate diagnostic utility for predicting fluid responsiveness independent of the equation used.
Does respiratory variation in inferior vena cava diameter predict fluid responsiveness in adult patients?